1991
DOI: 10.2307/4002309
|View full text |Cite
|
Sign up to set email alerts
|

Plant Community Responses to Short Duration Grazing in Tallgrass Prairie

Abstract: A key to management of short duration grazing systems is maintaining proper rest periods for individual pastures, but information on the necessary length of rest periods for tailgrass prairie is iimited. Research hypotheses for this study were that tallgrass prairie plant communities would respond differently to grazing schedules incorporating rest periods of varying lengths and that this response would be dependent on stocking rate. Treatments consisted of 3 grazing schedules (2,3, or 4 rotation cycles per 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 7 publications
2
18
1
Order By: Relevance
“…Pastures in both treatments were moderately grazed with mixed‐breed yearling cattle from about 1 December to 1 September, at 3 ha animal −1 based on long‐term research projects to optimize sustainable production (Gillen et al . 1991; McCollum et al .…”
Section: Methodsmentioning
confidence: 99%
“…Pastures in both treatments were moderately grazed with mixed‐breed yearling cattle from about 1 December to 1 September, at 3 ha animal −1 based on long‐term research projects to optimize sustainable production (Gillen et al . 1991; McCollum et al .…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that favorable amounts of precipitation during the growing season (Gillen et al, 1991), such as those that generally occur in the upper Midwest (Anderson and Matches, 1983), combined with low intensity defoliation (Forwood and Magai, 1992; Trocsanyi et al, 2009), and rest periods that follow native grass growth rates (Gillen and McNew, 1987; Mousel et al, 2003) can mitigate against potential injurious effects associated with defoliation. In this study, the above listed conditions were met.…”
Section: Discussionmentioning
confidence: 99%
“…The study area, Douglas County, is highlighted in the eastern part of the state. Gillen et al 1991;Anderson and Briske 1995;Collins and Steinauer 1998;Gillen et al 1998). The impact of grazing on plant communities depends upon how resistant species within the community are to grazing.…”
Section: Introductionmentioning
confidence: 99%